Effects of drip fertigation on production effect of mountain citrus orchard - WEN Mingxia; XI Hui; WU Shaohui; LI Na; CHEN Xijing (浙江大学学报. 农业与生命科学版)
Taking satsuma mandarin (Citrus unshiu Marc.) grown in mountainous areas as the research object, and custom fertilization of farmers (only applying chemical fertilizer, the input amounts of N, P2O5, K2O were 211.5, 180.0, 220.5 kg/hm2, respectively) as the control (CF), different combinations of fertilization with organic matter and chemical fertilizer decrement (DF1: the input amounts of N, P2O5, K2O were 153.0, 63.0, 157.5 kg/hm2, respectively; DF2: the input amounts of N, P2O5, K2O were 180.0, 108.0, 211.5 kg/hm2, respectively) were set to study the effects of drip fertigation on citrus yield, quality, nutrient absorption and soil fertility. The results showed that citrus yields of drip fertigation treatments with DF1 and DF2 increased by 17.5% and 16.4%, respectively, as compared with the control. The drip fertigation treatments with DF1 and DF2 could also increase fruit quality. The total soluble solid content increased by 11.4% and 10.5%, and vitamin C content increased by 26.7% and 13.6%, and the total acid content decreased by 16.2% and 21.6%, respectively, as compared with the control. In addition, drip fertigation treatments could significantly increase the absorption of calcium (Ca), magnesium (Mg) and boron (B) in leaves and fruits, which were higher than those of the control. Drip fertigation treatments also had a great impact on soil pH and soil fertility. The soil pH value of DF1 and DF2 treatments was higher than that of the control, and the organic matter content increased by 27.1% and 20.0%, respectively, and the hydrolysable nitrogen (N) content increased by 88.3% and 105.2%, respectively. The soil exchangeable Ca, exchangeable Mg and available B contents were also significantly higher than those of the control. It can be seen that while saving chemical fertilizer, drip fertigation can improve soil fertility, promote the nutrient absorption and utilization of leaves and fruits, and then increase citrus yield and improve fruit quality. Therefore, drip fertigation is an important measure to reduce chemical fertilizer application, improve quality and efficiency in citrus orchards.